Kelembagaan pengelolaan sumber daya pesisir Kota Gorontalo - Husain, Aryanto; Satria, Arif; Kusmana, Cecep; Eriyatno, Eriyatno (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
Along with the issues of economy growth and social complexities, potency of overlap and sectoral ignorance in coastal resources use tend to increase. This condition needs to be synergized so as the use of coastal resources can maintain the carrying capacity as well as contribute to social economy. This study aims at identifying and mapping stakeholder as well as analyzing their need in the future in regard with coastal resources management of Gorontalo City. Primary and secondary data were collected respectively from FGD and various documents and analyzed by using stakeholder analysis method. There were 26 stakeholder identified involved in coastal resources use in Gorontalo City. The stakeholder mapping showed five stakeholder as subject (high interest but low influence), twelve stash key player (high influence and high interest), seven stakeholder as setter context (high influence but low interest) and two belong to crowd (low interest and low influence). The stakeholder need analysis found that there is still gap in coordination mechanism among stakeholder. Also the result of working together to address common problem is also not yet optimum. There is a need to improve communication channel so as to build awareness and participation in coastal management issues of Gorontalo City